KUALITAS PELAYANAN DI MUSEUM KAMBANG PUTIH, TUBAN - Putri, Meita Pradani (Universitas 17 Agustus 1945 Surabaya, 2018)
This study was conducted to determine the quality of service in the Museum Kambang Putih, Tuban in providing services to visitors. This research is a qualitative descriptive study.The focus of research is based on five dimensions of the five dimensions of service quality (SERQUAL) by Parasuraman that is tangible, reliability, responsivenees, assurance, and empathy. These results indicate that the quality of service in the Museum Kambang Putih, Tuban already implementing tangible dimension, reliability, responsivenees, assurance and empathy and its indicators going pretty well. Dimensions responsivenees, assurance and empathy has been running very well and in line with expectations of visitors. But there are several dimensions and their indicators have not been going well and does not meet the wishes of visitors, among other tangible dimension to the indicators amenities to make the inconvenience visitors in museum and includes facilities are not complete, as well as dimensional reliability indicator of officers in the field of education is not in the room so the clerk there and help provide information on the collections and historic objects, due to the lack of education officials in the Museum Kambang Putih, Tuban.Keywords: Quality of Service, Public Service, Museum